Kajian Dampak Sosial Terhadap Keberadaan Perusahaan HPH di Propinsi Sumatera Barat - Zamzami, Lucky (Humanus, 2011)
This research purposed are to know social impact of foresty management done by HPH Company and influence to community around forest, conducted in Solok Selatan Regency, to know depended level of community to forest and nature resource as basic needs and specifying the target of change which wish to be reached and recommended the best approach for improving benefit of foresty management to community and also participated of community in the effort forest everlasting. This research use qualitatif method with observation, indepth interview and Focus Group Discussion (FGD). Result of reseacrh show that the forest is very important for community as protected area from flood disaster and dryness and as wood source for cummunity. But, until now condition of forest felt having changes or degradation, especially felt from climate change side and quantity and quality water changes. There is a negative responce about HPH company existence, mostly happened because lack of socialization and communications among side. Effort of repair recommended are to develop more condusif relation between government, community with company, with interest many socialization and communications to find best solutions to the all problem. Key words: Local Community, HPH Forest Area, Foresty Management, Social Impact